Fenton reaction-independent ferroptosis therapy via glutathione and iron redox couple sequentially triggered lipid peroxide generator. (May 2020) - He, Yu-Jing; Liu, Xiao-Ying; Xing, Lei; Wan, Xing; Chang, Xin; Jiang, Hu-Lin
Abstract: Ferroptosis, a newfound non-apoptotic cell death pathway, results from the accumulation of iron-dependent lipid peroxide (LPO). Recently, emerging iron-based nanomaterials have been extensively developed to induce Fenton reaction-dependent ferroptosis for cancer therapy. However, insufficient amount of H2 O2 and limited acidity of tumor could not satisfy the optimal conditions for Fenton reaction, which extremely limited the efficacy of ferroptosis therapy. Herein, we report a novel glutathione (GSH) and iron redox couple sequentially triggered LPO generator (LPOgener) which can directly supply the Fenton reaction-independent downstream executioner of ferroptosis for cancer therapy. By harnessing GSH-mediated Fe 3+ reduction and the well-established iron redox couple-mediated lipid peroxidation, LPOgener was constructed by complete ferric ammonium citrate (FAC) and unsaturated lipids-rich phosphatidylcholine, and formed as FAC loaded liposome. The Fe 3+ encapsulated in LPOgener could be efficiently reduced to Fe 2+ under high GSH level in tumor cells. Subsequently, the formed iron redox couple could trigger overwhelming lipid peroxidation for Fenton reaction-independent ferroptosis. Superior anticancer therapeutic effect with little systemic toxicity demonstrated that LPOgener was a potent ferroptosis-inducing agent for cancer therapy. Therefore, to directly supply the druglike, easily prepared, GSH and iron redox couple sequentially triggered LPOgener would provide a new direction in designing strategies for ferroptosis therapy. Graphical abstract: Image 1